Perception and knowledge of dietary supplements use among University Students from Lahore Pakistan - Riaz, Muhammad Waseem; Azam, Muhammad Saad; Ashraf, Shiza; Butt, Nauman Ismat; Waris, Barak; Ghoauri, Muhammad Sohail Ajmal (Utan Kayu Publishing, 2025)
Background & Objective: Dietary supplementation has gained popularity, particularly among the young population, but their knowledge and attitudes toward these supplements remain underexplored. Understanding their level of knowledge and perceptions is essential for promoting informed and responsible use of dietary supplements. The present study aimed to assess the knowledge and practices toward dietary supplementation among university students, focusing on their awareness, reasons for use or non-use. Methods: This descriptive cross-sectional study was conducted at Superior University Lahore Pakistan. Eighty university students of both genders were enrolled in the study after taking informed consent using non-probability consecutive sampling technique. Students with a present or past diagnosis of nutritional deficiencies were excluded. Demographic information was noted. A structured questionnaire comprising of 2 domains was filled by the participants: first domain was regarding knowledge of dietary supplementation; and second domain was about practices. All the data was entered into SPSS version 26 for analysis. Results: Majority of the participants (45, 56.2%) were aged ≤25 years and 51 (63.7%) were females. Seventeen (21.2%) were postgraduate while 63 (78.8%) were graduate level students. Most of the participants (42, 52.5%) belonged to middle socioeconomic status. In the present study 39 (48.8%) had heard of dietary supplementation and 33 (41.3%) reported using dietary supplementation themselves. The most common reasons for using dietary supplementation were for cosmetic reasons (16, 20.0%) and for weight loss (09, 11.2%). The most common reasons for not using dietary supplementation were expensiveness (19, 23.7%) and fear of adverse effects (13, 16.3%). Conclusion: While nearly half of the participants had heard of dietary supplementation, a smaller percentage were actually using supplements, with cosmetic reasons and weight loss being the most common motivations. These findings highlight the need for further education on the benefits, risks, and affordability of dietary supplements, especially among younger populations.